Pelaksanaan Izin Mendirikan Bangunan Hotel Di Kota Yogyakarta - Christy Ayu Saputri; Purwono Sungkowo Raharjo (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
The Analysis of Hotel Building Permits Supervision and Implementation in Yogyakarta. This essay focuses on state administrative law in legal study program, law faculty, UNS Surakarta. This research aims to determine (1) yogyakarta city government's policy on Supervision in Granting Implementation of Hotel Building Permits in Yogyakarta; and (2) Yogyakarta City Government's role in controlling hotel construction to minimalize environmental impact. This research is a legal research empirical sociological approach. To achieve these objectives, the researcher used data collection techniques through observation, interviews, and documentation. The results of this study indicate that: (1) to minimalize environmental impact loss caused by hotel construction, the City of Yogyakarta government issues a policy on controlling hotel construction through Yogyakarta Mayor Regulation No. 85 of 2018. The aim is to provide supervision and restrictions in granting permits for hotel construction. (2) New policy at the stage of supervision procedures for hotel construction requires cooperation between agencies namely DPMP and DPUPKP Yogyakarta City to verify field reviews, but the determination of the policy is not in line with the existing implementation so it is not effective. (3) The Environmental Permit from the Environment Agency or local authority has an important role in the process of minimizing the risk of environmental impacts. Mandatory of environmental impact assessment and UKL-UPL are one of the efforts to control and to plan that must be fulfilled by the initiator.